Application of the Hungarian Method in Workforce Scheduling Optimization at the Magetan Dynamic Vegetable-Tanned Leather Sandal Industry - Nafisyatul Azizah; Putri Amelia Hanifa; Revania Eka Putri Devitasari; Rizka Tri Wahyuni; Lisnani Lisnani; Sumarni Sumarni (JES-MAT: Jurnal Edukasi dan Sains Matematika, 2025)
Task allocation at the Dinamis Magetan vegetable-tanned leather sandal industry is currently handled flexibly, based on workers' general availability rather than a systematic evaluation of individual processing-time efficiency, creating a risk of inconsistent completion times across its five sequential production stages. Although the Hungarian Method has been widely applied to optimize labor assignment across various Indonesian MSME sectors, its application to traditional craft industries with a flexible, multi-skilled workforce — such as vegetable-tanned leather sandal production, where workers are trained to master every stage ("pinter kabeh") rather than remain fixed to one station — remains largely unexamined. This study addresses that gap through a descriptive quantitative case study involving five workers, selected via stratified random sampling to represent five main production units: Design and Pattern, Upper Production, Insole Production, Assembly, and Finishing. Processing-time data were collected through observation, interviews, and documentation, analyzed manually using the Hungarian Method, and verified using the POM-QM application for Windows. The results show that the optimal assignment places Worker 1 in Design and Pattern, Worker 2 in Upper Production, Worker 3 in Insole Production, Worker 4 in Assembly, and Worker 5 in Finishing, yielding a minimum total processing time of 73 minutes per production cycle — a result consistent between manual and software calculations, and closely matching the factory's actual reported daily output. These findings indicate that, for this case, the Hungarian Method can be applied accurately and consistently to obtain an optimal assignment solution, offering craft-based MSMEs a low-cost, evidence-based reference point for workforce allocation decisions that can be adopted alongside their existing flexible rotation systems.